2022
DOI: 10.3390/ijms23095155
|View full text |Cite
|
Sign up to set email alerts
|

A Blueprint of Microstructures and Stage-Specific Transcriptome Dynamics of Cuticle Formation in Bombyx mori

Abstract: Insect cuticle is critical for the environmental adaptability and insecticide resistance of insects. However, there is no clear understanding of the structure and protein components of the cuticle during each developmental stage of holometabolous insects, and knowledge about the protein components within each layer is vague. We conducted serial sectioning, cuticular structure analysis, and transcriptome sequencing of the larval, pupal, and adult cuticles of Bombyx mori. The deposition processes of epicuticle, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…These findings suggested that the 32 CP genes are indispensable and that other CP genes may have redundant and complementary functions ( Pan et al, 2018 ). Previous studies revealed that the construction of the larval cuticle of silkworms requires the precise expression of more than two hundred CP genes ( Yan et al, 2022 ). The production, interaction, and deposition of CPs and pigments are complex and precise processes, and our research showed that Bm-mamo plays an important regulatory role in this process in silkworm caterpillars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggested that the 32 CP genes are indispensable and that other CP genes may have redundant and complementary functions ( Pan et al, 2018 ). Previous studies revealed that the construction of the larval cuticle of silkworms requires the precise expression of more than two hundred CP genes ( Yan et al, 2022 ). The production, interaction, and deposition of CPs and pigments are complex and precise processes, and our research showed that Bm-mamo plays an important regulatory role in this process in silkworm caterpillars.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to pigment synthesis, the microstructure/nanostructure of the body surface and wing scales are important factors that influence body color patterns. The body surface and wing scales of Lepidoptera are composed mainly of cuticular proteins (CPs) ( Liu et al, 2021 ; Yan et al, 2022 ). There are multiple genes encoding CPs in Lepidopteran genomes.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggested that the 32 CP genes are indispensable and that other CP genes may have redundant and complementary functions ( 76 ). In previous studies, it was found that the construction of the larval cuticle of silkworms requires the precise expression of more than two hundred CP genes( 22 ). The production, interaction, and deposition of CPs and pigments are complex and precise processes, and our research showed that Bm-mamo plays an important regulatory role in this process in silkworm caterpillars.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to pigment synthesis, the microstructure/nanostructure of the body surface and wing scales are important factors that influence body color patterns. The body surface and wing scales of Lepidoptera are mainly composed of cuticular proteins (CPs) ( 21, 22 ). There are multiple genes encoding CPs in Lepidopteran genomes.…”
Section: Introductionmentioning
confidence: 99%
“…The CPG family features multiple GGYGG or GGxGG repeats (Futahashi et al, 2008), and the CPCFC family contains two or three repetitive C‐X5‐C motifs (Ioannidou et al, 2014). These comprehensive classifications offer better understanding of the diversity and complexity within insect CPs, shedding light on their essential roles in the intricate biology of insects (Yan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%